Corporate Governance Engineering of Islamic Banking and Finance: Tantangan Globalisasi Sistem Ekonomi dan Pasar Bebas - Budi Sukardi (TSAQAFAH, 2013)
The development of Islamic banking indicated dynamic changes and rapid growth. Some countries such United States, United Kingdom, European Union, Canada, Singapore implemented the Islamic financial system. However, economic globalization, laissez-faire, and financial crisis that engulf Indonesia as consequence the lack of bankers commitment to corporate governance, regulation and supervision of the government,business climate of banking do not prioritize business ethics between investors and bankers. Emerging debate that the models of corporate governance developed in western countries can not applicable in Muslim countries, even countries with high levels of corruption. Both models oscillated to find solution in fulfill stakeholders which the principles of morality have been ignored. The Implementation of corporate governance became part of social responsibility, values, ethics and norms must be possessed by Islamic banking due to highly correlated with the organizational readiness and the alignment of management actions to satisfy and ser ve stakeholder needs ,giving an exclusive deals in compliance the justice of morality ,social welfare,economic and political system, corporate image and accountability in keeping the identity of Islam as a religion. Corporate governance became a value system in Islamic financial institutions which giving same legal protections to all stakeholders, it would have an impact the effectiveness, the sustainability of institutions and generate trust with security sense of the community ,financial efficiency ,fiscal and monetary policies resulting in financial equilibrium.